Implementasi Penggunaan Topologi Jaringan pada Instalasi WiFi di Fakultas Keguruan dan Ilmu Pendidikan Untirta - Didik Aribowo; Norma Suci Pratiwi; Christin Hutagaol; Nadjwa Nabila Rachman; Mochamad Zacky Ilham Halim; Faqih Nazrul Hakim; Ravianri Putra Dinata; Azhar Mahdi; Fahri Ismail Haniya (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The installation of WiFi networks in the campus environment plays a very vital role in supporting the smooth running of learning processes, research, and other operational activities. At the Faculty of Teacher Training and Education (FKIP) of Sultan Ageng Tirtayasa University, the implementation of WiFi networks has become a focus in efforts to improve information technology infrastructure. This study discusses the application of network topology in WiFi installations in the FKIP environment using literature study methods and direct observation in the field. Based on the results of the study, the network topology used is a tree topology. This topology is a combination of bus topology and star topology, which allows the distribution of network connections widely throughout the faculty building. The choice of tree topology is considered effective because it can expand the network coverage and maintain connection stability. In addition to the topology aspect, the network authentication system has also undergone significant changes. Initially using the Single Sign-On (SSO) method, the system then switched to using Access ID. This shift aims to improve ease of user access and provide flexibility in the use of various types of devices. Overall, this study shows that the implementation of tree topology and Access ID authentication system has succeeded in improving the quality of network services in the FKIP academic environment.